Participation of Teachers and Parents in the PAUD Parenting Program in Banjarmasin - Maulidha; Noor Amaliah Puteri; Rasunnah; Mariam; Widyawati (MultiTech Publisher, 2023)
Parenting is A combining activities _ education received by children _ at school and at home . On activities This is coordination between teachers and parents students are very necessary . Study This explore How role as well as teachers and parents at the PAUD IT Assunah parenting program in Banjarmasin. Study done with use method qualitative . Primary data was obtained from interview in- depth and secondary data through document parenting activities at school . Then done data reduction and withdrawal conclusion . The result there is three stages parenting activities, namely , planning , implementation , and evaluation . Then parents _ has role active in parenting activities with fill in parenting activities through student parent association as _ resource person , consumption and presenter and teacher as the coordinator.